A Digitized Inventory of Domestic Animal Resources of India - Yadav, Dinesh Kumar; S.P. Dixit (Journal of Livestock Biodiversity, 2025)
A comprehensive digitized inventory of India’s domestic animal resources provides data on livestock species: cattle, buffalo, sheep, goat, equine, camel and poultry. It offers information in seven modules on geographical distribution; morphological description and diagnostic features; performance; livestock farms; products and byproducts; market information, trade data and patents. It also provides colored photographs of male and female animals of each breed of above-mentioned animal species. It uses secondary data on different aspects of each breed of different species. The data was standardized using database normalization techniques and the same was then converted into database format using a relational database management system (RDBMS). The system is menu driven designed using MS-Access at the back end and Visual Basic 6.0 at the front end. A user-friendly graphical user interface has been developed for storage and retrieval of information from the database. The database system provides information on different aspects of domestic animal resources at a single/uniform platform, which can be of use to a wide range of users from students, teachers, planners, administrators, policy makers, farmers, dairy industry, patent offices and the scientific community at large